European influence in ITU-R: The end of an era of dominance? - Mohamed El-Moghazi; Jason Whalley; James Irvine (International Telecommunications Society (ITS), 2013)
Since its establishment in 1865, the ITU has been considered by many as a European organisation as it was controlled by small number of European countries. Due to the conflict of interests between the European countries and other countries, the world was divided into three regions in terms of radiocommunication service allocation where the European, African and the Arab countries lie in Region 1 of the Radio Sector of the ITU (ITU-R). However, recent years have witnessed a change in the power balance within Region 1 where the Arab and African countries called in the World Radiocommunication Conference of 2012 (WRC-12) for an immediate allocation of the spectrum in the 694-790 MHz band to mobile service noting that the issue was not on the agenda of the conference. WRC-12 eventually agreed to the allocation to be effective immediately after WRC-15 after resistance mainly from the European countries...
Keywords: 330